Foregrounding co-artistry in an aesthetic and plurilingual/pluriliteracies approach to additional language teaching and learning - Albuquerque, Diego L.; Moore, Emilee (Frontiers in Education, 2024)
In this article, we propose an aesthetic and plurilingual/pluriliteracies approach to additional (or second, foreign…) language teaching and learning. The research reported on took place in a secondary school in Barcelona where young people take on the role of teachers of the host languages (i.e., Catalan and Spanish) to adult migrants. We focus on a plurilingual poetry workshop offered in this program as an empirical foundation for the proposed approach. Data was collected ethnographically during the poetry workshop (i.e., through participant observation, field notes, conversations, video, photography) allowing the exploration of processes and outcomes. We consider, on the one hand, the opportunities for language learning made possible by incorporating arts-based methods and plurilingualism/pluriliteracies in the workshop. On the other hand, we ask what an aesthetic lens, combined with a recognition of plurilingualism/pluriliteracies, can offer to our understanding of language learning outcomes. Our results suggest that co-artistry is an opportunity for enhancing additional language learning in our aesthetic and plurilingual/pluriliteracies approach to additional language teaching and learning.